2020
DOI: 10.4025/actascibiolsci.v42i1.48714
|View full text |Cite
|
Sign up to set email alerts
|

Pollen resources partitioning of stingless bees (Hymenoptera: Apidae) from the southern Atlantic forest

Abstract: Meliponinae eusocial bees are among the most important pollinators in the Neotropics and their beekeeping has been growing as both recreational and economic activity. Information on the pollen preferences and niche overlap among species coexisting in the same location is still scarce. This study focused on the use of pollen resources by three native species of Meliponinae in the Atlantic Forest, Melipona quadrifasciata quadrifasciata (Lepeletier 1836), Scaptotrigona depilis (Moure 1942), and Tetragonisca angus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
1
2
0
3
Order By: Relevance
“…In the pollen spectrum, there was a predominance of pollen types related to shrubby and arboreal plants. Similar results were found by Rodrigues et al (2020), who evaluated the pollen resources collected by stingless bees in a fragment of Atlantic forest and reported that arboreal and shrubby species were more intensely and frequently visited. According to Ramalho (2004), stingless bees concentrate their collection efforts in the upper layer of vegetation in the Atlantic Forest environments, searching for massive flowering.…”
Section: Discussionsupporting
confidence: 86%
“…In the pollen spectrum, there was a predominance of pollen types related to shrubby and arboreal plants. Similar results were found by Rodrigues et al (2020), who evaluated the pollen resources collected by stingless bees in a fragment of Atlantic forest and reported that arboreal and shrubby species were more intensely and frequently visited. According to Ramalho (2004), stingless bees concentrate their collection efforts in the upper layer of vegetation in the Atlantic Forest environments, searching for massive flowering.…”
Section: Discussionsupporting
confidence: 86%
“…The teachings are followed and improved by the younger ones, and some members of the community are seen as great connoisseurs of the subject. The products from bees are used in handicrafts, religious rituals and medicinal potions, as well as activities related to spiritual and contemplative life [47]. A study was conducted on the traditional knowledge about the SBs of the Enawene-Nawe people of the state of Mato Grosso.…”
Section: Indigenous Bees: Sociocultural Importance and Ethnoknowledgementioning
confidence: 99%
“…Observa-se na literatura estudada que são escassas as informações sobre área de distribuição natural das ASFs e suas preferências polínicas, produtividade, manejo correto das colônias, características físico-químicas dos méis e demais produtos que podem ser gerados desta atividade em especial com potencial para suplementação alimentar (BRATMAN, 2020;FELIX;FREITAS, 2021;RODRIGUES;et. al., 2020 Mohammad;.…”
Section: Justificativaunclassified
“…Brasil existem diversas espécies adaptadas aos diferentes biomas, o que possibilita desenvolver a meliponicultura como atividade econômica viável em todo o território nacional MOHAMMAD;SANTOS, et.al. 2021;FELIX;FREITAS, 2021;RODRIGUES;. A quantidade de espécies é estimada uma vez que novas são de descobertas e outras se extinguem em razão da interferência humana.…”
Section: Introductionunclassified